Anxiety in children and adolescents. Issue 11 (November 2019) - Poppleton, Aaron; Ramkission, Roshelle; Ali, Sidra
Anxiety is the physiological state of fear, unease or apprehension experienced by an individual in the face of an uncertain outcome. Anxiety disorders are characterised by recurrent symptoms of anxiety disproportionate to the eliciting situation, and are the most common disorders of emotion among young people in the UK. They have an early onset and increasing prevalence. This article provides a detailed insight into causes, diagnosis and management strategies for the different anxiety disorders in young people within primary care and the wider community.